Teaching and Learning on the Edge of a Pandemic: Providing Continuity and Re-building an Online Learning Community - Eleonora Bâcă (Ovidius University Annals: Economic Sciences Series, 2020)
The present analysis investigates the effects of an unprecedented situation which occurred during the pandemic of COVID-19 outbreak, when the entire education system had to transfer in the online medium- a form of extreme blended learning adapted to unique circumstances. The present study is meant to offer an insight into a “bleak” period from which lessons are to be learnt and systems to be adjusted. We strongly believe that difficulties should be embraced and seen as perspectives of growth. The article is based on a survey containing a number of 14 questions concerning the use of virtual instruments and learning platforms, the challenges encountered by students during this online period and the impact of these. The survey was carried out on a number of 128 students enrolled in the 2nd year at the Faculty of Economic Sciences, at “Ovidius” University of Constanța.